Behaviour of discontinuous precast concrete beam-column connections - Hasan, Sarakot (2011)
The study investigates experimentally and theoretically the behaviour of an internal precast concrete beam-column connection, where both the column and beam are discontinuous in construction terms. The aim was to modify the behaviour mechanisms within the connection zone by introducing a beam hogging moment resistance capacity under dead loads and limiting the damage within the connection. This is to offer permanent dead load hogging moments that could counterbalance any temporary sagging moment generated under sway loads, enhance the rotational stiffness, balance the design requirements for the beam-end and beam mid-span moments, provide efficient continuity across the column, and reduce the deflection at the beam mid-span.